Performance evaluation of different types of graphite electrodes on titanium (Ti - 6A1 - 4V) - Abdul Haq, Reazul Haq (2009)
This thesis presents the EDMing of Titanium (Ti-6A1-4V) using POCO EDM 3 and POCO EDM C3 graphites electrodes with diameter of 10 mm. The main purpose of this study was to investigate the influenced of various parameters involved in EDM on the machining characteristics, namely, material removal rate (MRR), electrode wear ratio (EWR), surface roughness (Ra), recast layer (RL) and heat affected zone (HAZ) after undergone EDMing process and to compare the performance of both electrodes. The Full Factorial Design of Experiment (DOE) approach with two-level was used to formulate the experimental layout, to analyze the effect of each parameter such as pulse on (ON), pulse off (OFF), peak current (IP) and servo voltage (SV) on the machining characteristics EDM . In this investigation, the machining operation for titanium was performed using a Sodick linear motor EDM sinker series AQ55L. Meanwhile, for the measurement equipments; Mitutoyo Surftest SJ-400 was used to measure the surface roughness, and the thickness of recast layer and heat affected zone were examined using the Scanning Electron Microscope XL40. In general, results revealed that pulse on (ON) and peak current (IP) have appeared to be the most significant effect to all responses investigated. In term of performance, POCO C3 gives better material removal rate (MRR) value compare to POCO 3 but in term of electrode wear ratio (EWR) and also surface roughness (SR) POCO 3 gives better result compare to POCO C3. On the Recast layer and HAZ both the good and the worst came from POCO 3. The lowest recast layer achieved was 13.5 fxm and the lowest HAZ achieved was 12.7 Hm. Confirmation tests were also conducted for the optimum conditions for each machining characteristics in order to verify and compare the results from the theoretical prediction using Design Expert software and experimental confirmation tests. Overall, the results from the confirmation tests showed that the percentage of performance was acceptable due to all the results obtained were within the allowable values which was less than 15% of margin error.